Enhancing academic certificate privacy with a hyperledger fabric blockchain-based access control approach - Saleh, Omar S.; Ghazali, Osman; Idris, Norbik Bashah (Springer Nature, 2023)
Academic credentials hold great significance as they portray a person's educational qualifications, which have a substantial impact on their future achievements. Nevertheless, these certificates are often exposed to various security risks like unauthorized access, forgery, and tampering, as conventional access control mechanisms such as passwords or physical documents are inadequate to ensure their privacy and safety. This research presents a fresh approach to access control, employing the Hyperledger Fabric blockchain technology to secure academic certificates' privacy. The suggested access control protocol intends to guarantee that only authorized individuals have access to academic certificates, thus ensuring their privacy and safeguarding them from any unauthorized access. The methodology involved identifying stakeholders and determining their roles and required permissions. Students are granted full permissions, while other parties can only read and execute the certificates. The protocol is designed with ihe following two functions: locking and unlocking the certificate. When a student locks their certificate, it becomes unreadable to any other party, including the issuing university. The certificate can only be unlocked by the certificate owner, making it readable by authorized parties like potential employers or verification services. The study's results demonstrate that the proposed access control protocol is effective in protecting academic certificates' privacy while ensuring appropriate access control. The protocol allows students to lock and unlock their certificates, giving them complete control over their certificates' privacy. Only authorized parties can access the certificates, and their access is limited to reading and executing the certificates. The proposed protocol's performance was evaluated through performance evaluation, indicating that it has a high throughput rate and low latency. The protocol's effectiveness was tested through various use cases by varying the specifications of key parameters, and the results show that the protocol has high throughput and low latency at different transaction rates.